1996
DOI: 10.1007/bf00176674
|View full text |Cite
|
Sign up to set email alerts
|

An approach to mapping haplotype-specific recombination sites in human MHC class III

Abstract: Studies of the major histocompatibility complex (MHC) in mouse indicate that the recombination sites are not randomly distributed and their occurrence is haplotype-dependent. No data concerning haplotype-specific recombination sites in human are available due to the low number of informative families. To investigate haplotype-specific recombination sites in human MHC, we here describe an approach based on identification of recombinant haplotypes derived from one conserved haplotype at the population level. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…96 This particular hotspot is not present in the corresponding region in humans, but there is evidence from a detailed analysis of an MHC haplotype for a recombinational hotspot around the TNF locus (i.e., telomeric to the HSPA1A/B-HLA-DRB fragment). 97 As expected, complotypes show stronger LD with HLA-DRB1 98 and our results suggested that the HSPA1B locus would be in stronger LD with HLA-DRB1. Thus, the HSPA1A/B polymorphisms may be considered as MHC class III lineage markers as they show correlations with evolutionarily ancient HLA class II lineages.…”
Section: Discussionsupporting
confidence: 80%
“…96 This particular hotspot is not present in the corresponding region in humans, but there is evidence from a detailed analysis of an MHC haplotype for a recombinational hotspot around the TNF locus (i.e., telomeric to the HSPA1A/B-HLA-DRB fragment). 97 As expected, complotypes show stronger LD with HLA-DRB1 98 and our results suggested that the HSPA1B locus would be in stronger LD with HLA-DRB1. Thus, the HSPA1A/B polymorphisms may be considered as MHC class III lineage markers as they show correlations with evolutionarily ancient HLA class II lineages.…”
Section: Discussionsupporting
confidence: 80%
“…The birthplaces in Figure 2C are more scattered, but it should be noted that they actually represent four distinct recombinant haplotypes, all demonstrated to have originated from the A3 Cw6 B47 F10 DR7 haplotype. 19 By studying each recombinant separately, clear clustering can be observed. For example, those with B18 follow the route of the Lestijoki river ( Figure 2C).…”
Section: Geographic Origin Of Haplotypesmentioning
confidence: 99%
“…Studies in mice suggest that MHC recombination preferentially occurs in certain regions (hot spots) (10, 11). Recombination frequencies do vary in a haplotype‐dependent manner in the mouse MHC (12), but despite suggestions of a similar situation in humans (13, 14), the large number of haplotypes and uncontrollable mating patterns preclude the ability to draw similar conclusions. In this sense, it has been tested in the 12th International Histocompatibility Workshop whether certain alleles from HLA‐B locus were more commonly involved than others in recombinations (11).…”
Section: Resultsmentioning
confidence: 99%